Laser Fabrication of Graphene-Based Electronic Skin - Liu, Yu-Qing; Chen, Zhao-Di; Mao, Jiang-Wei; Han, Dong-Dong; Sun, Xiaoying (Frontiers in Chemistry, 2019)
Graphene is promising for developing soft and flexible electronic skin. However, technologies for graphene processing is still at an early stage, which limits the applications of graphene in advanced electronics. Laser processing technologies permits mask-free and chemical-free patterning of graphene, revealing the potential for developing graphene-based electronics. In this minireview, we overviewed and summarized the recent progresses of laser enabled graphene-based electronic skins. Two typical strategies, laser reduction of graphene oxide (GO) and laser induced graphene (LIG) on polyimide (PI), have been introduced towards the fabrication of graphene electronic skins. The advancement of laser processing technology would push forward the rapid progress of graphene electronic skin.